The Effect of Special Proposed Exercises Using Circuit Style on Some Types of Muscular Strength and Achievement in Disabled Iraqi League Weightlifters - Aljorani, Ali (Journal of Physical Education, 2023)
The research aimed at identifying the effect of special exercises using circuit training on some types of muscular strength (relative strength, speed – strength, strength endurance) and achievement in disabled weightlifters. The researchers used the experimental method on (10) weightlifters. The subjects were (8) weightlifters whom participated in Qatar’s Championship in 2021; (4) weightlifters as the experimental group and (4) as controlling group. The researcher used special exercises with high intensity interval training as well as circuit training. The data was collected and treated to conclude that there are statistical differences between pre and posttests in favor of posttests. The experimental group showed significant differences in relative strength, strength endurance, and achievement but in speed – strength there were no significant differences. Finally, the researcher concluded that the proposed exercises using circuit training develop some types of muscular strength and achievement compared to other types of training.